Characterization of sewage sludge generated in Rio de Janeiro, Brazil, and perspectives for agricultural recycling - Alan Henrique Marques de Abreu (Semina: Ciências Agrárias, 2017)
Sanitary sewage collection and treatment is a serious environmental problem in Brazilian cities, as well as the destination of solid waste resulting from this process, i.e. the sewage sludge, a substance rich in organic matter and nutrients, which is normally discarded in landfills. The aim of this study was to characterize the sewage sludge generated in four treatment stations in Rio de Janeiro State, Brazil and check if they meet the legal criteria of the National Environment Council (CONAMA), Resolution No. 375/2006. It also focused on analyzing the perspectives for its agricultural recycling based on the potential demand for main agricultural crops grown in Rio de Janeiro State. Samples from eight sewage sludge lots from four treatment stations located in the metropolitan area of Rio de Janeiro were analyzed. These stations receive and treat only domestic sewage by activated sludge system. For chemical and biological characterization of these lots, representative samples were collected and analyzed according to parameters of CONAMA Resolution No. 375/2006. In order to analyze the perspectives of agricultural recycling of sewage sludge in Rio de Janeiro State, 10 crops with the largest cultivated area in the state were surveyed and analyzed which of them are apt to receive sewage sludge as fertilizer and/or soil amendment. To determine the potential demand for sewage sludge in agriculture, the area occupied by these crops were multiplied by each fertilizer recommendation considering the sewage sludge as fertilizer. The analyzed sludge presented a high content of nutrients and organic matter and was included in the parameters of heavy metals, pathogenic agents, and bacteriological indicators stipulated by CONAMA Resolution No. 375/2006. The agricultural panorama of Rio de Janeiro State is favorable for agricultural recycling of sewage sludge since there is a great potential demand for this residue and, among the 10 agricultural crops with the largest cultivated area in the state, sludge can be used as fertilizer or soil amendment in eight of them. The implementation of a State Sewage Sludge Recycling Program could dispose of this material in a more sustainable way, as well as improve the quality of agricultural soils and reduce costs with chemical fertilizers, bringing positive results for sanitation companies and producers.